Itraconazole in the Treatment of Nonfungal Cutaneous Diseases: A Review - Ya-Chu Tsai; Tsen-Fang Tsai (Adis, Springer Healthcare, 2019)
Abstract Introduction The anti-inflammatory and pro-kinetic properties of antibiotics have been widely reported. However, the non-antifungal properties of antifungal agents are less well known and less explored in clinical practice. The purpose of this review was to survey the literature on the non-antifungal use of itraconazole in dermatological practice and the possible modes of action of this agent. Methods The PubMed database was searched for relevant articles published up to January 2017. The references in the articles identified by the search were then hand-searched for additional relevant publications. Results Itraconazole displays a great diversity of non-antifungal activity and has been used to treat a broad spectrum of diseases. The results of our survey reveal that itraconazole has the potential to be an alternative agent for treating patients with advanced cancer (either alone or in combination with other cytotoxic chemotherapeutic drugs), especially those refractory to traditional treatments. Moreover, itraconazole acts as an anti-angiogenesis agent, induces nail growth, and modulates inflammatory or immune diseases. Conclusion Oral antifungal agents have many non-antifungal properties. However, the body of evidence on individual agents often remains limited due to the lack of large-scale randomized controlled studies. Although some of the findings published to date seem promising, pharmacological vigilance should be taken for off-label use in real-world practice.